Intellectual property in construction - Rohovyi, Stanislav; Yurchenko, Oksana (Academic journal Industrial Machine Building Civil Engineering, 2021)
The article considers the economic approach to the assessment of intellectual property rights. The place and role of intellectual property in the activities of construction entities are described. The purpose of the article is a comprehensive analysis of the place and role of intellectual property in the concept of economic sustainability of construction companies, as well as identifying the most important areas and practical measures to intensify the use of intellectual property in their activities. Achieving the goal was solved by methods of theoretical research on intellectual property issues of the construction industry; research of innovations in the field of theory and practice of construction production